Evolution of breeding plumages in birds: a multiple-step pathway to seasonal dichromatism in New World Warblers (Aves: Parulidae) - Terrill, Ryan; Wolfe, Jared; Seeholzer, Glenn (Dryad, 2020)
Many species of birds show distinctive seasonal breeding and nonbreeding
plumages. A number of hypotheses have been proposed for the evolution of
this seasonal dichromatism, specifically related to the idea that birds
may experience variable levels of sexual selection relative to natural
selection throughout the year. However, these hypotheses have not
addressed the selective forces that have shaped molt, the underlying
mechanism of plumage change. Here, we examined relationships between
life-history variation, the evolution of a seasonal molt, and seasonal
plumage dichromatism in the new world warblers (Aves: Parulidae), a family
with a remarkable diversity of plumage, molt, and life history strategies.
We used phylogenetic comparative methods and path analysis to understand
how and why distinctive breeding and nonbreeding plumages evolve in this
family. We found that color change alone poorly explains the evolution of
patterns of biannual molt evolution in warblers. Instead, molt evolution
is better explained by a combination of other life-history factors,
especially migration distance and foraging stratum. We found that the
evolution of biannual molt and seasonal dichromatism are decoupled, with a
biannual molt appearing earlier on the tree, more dispersed across taxa
and body regions, and correlating with separate life-history factors than
seasonal dichromatism. This result helps explain the apparent paradox of
birds that molt biannually but show breeding plumages that are identical
to the nonbreeding plumage. We find support for a two-step process for the
evolution of distinctive breeding and non-breeding plumages: that
prealternate molt evolves primarily under selection for feather renewal,
with seasonal color change sometimes following later. These results reveal
how life history strategies and a birds’ environment act upon multiple and
separate feather functions to drive the evolution of feather replacement
patterns and bird coloration.
See Manuscript.